Effects of Beef Protein Supplementation in Male Elite Triathletes: A Randomized, Controlled, Double-Blind, Cross-Over Study. (2nd January 2021) - Valenzuela, Pedro L.; Montalvo, Zigor; Mata, Fernando; González, Manuela; Larumbe-Zabala, Eneko; Naclerio, Fernando
Abstract: Objective: Beef protein extracts are growing in popularity in recent years due to their purported anabolic effects as well as to their potential benefits on hematological variables. The present randomized, controlled, double-blind, cross-over study aimed to analyze the effects of beef protein supplementation on a group of male elite triathletes (Spanish National Team). Methods: Six elite triathletes (age, 21 ± 3 years; VO2max, 71.5 ± 3.0 ml·kg·min −1 ) were randomly assigned to consume daily either 25 g of a beef supplement (BEEF) or an isoenergetic carbohydrates (CHO) supplement for 8 weeks, with both conditions being separated by a 5-week washout period. Outcomes, including blood analyses and anthropometrical measurements, were assessed before and after each 8-week intervention. Results: No effects of supplement condition were observed on body mass nor on skinfold thicknesses, but BEEF induced significant and large benefits over CHO in the thigh cross-sectional area (3.02%, 95%CI = 1.33 to 4.71%; p = 0.028, d = 1.22). Contrary to CHO, BEEF presented a significant increase in vastus lateralis muscle thickness (p = 0.046), but differences between conditions were not significant (p = 0.173, d = 0.87). Although a significantly more favorable testosterone-to-cortisol ratio (TCR) was observed for BEEF over CHO (37%, 95% CI = 5 to 68%; p = 0.028, d = 1.29), no significant differences were found for the hematological variables (i.e., iron, ferritin, red blood cell count, hemoglobin or hematocrit). Conclusion: Beef protein supplementation seems to facilitate a more favorable anabolic environment (i.e., increased TCR and muscle mass) in male elite triathletes, with no impact on hematological variables.